KEPEMIMPINAN TRANSFORMATIF BERBASIS NILAI PROFETIK DALAM OPTIMALISASI PENGELOLAAN BIAYA OPERASIONAL PENDIDIKAN DI MADRASAH IBTIDAIYAH KECAMATAN PURWOKERTO BARAT - Lestari, Sri; Ali Muhdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Madrasah Ibtidaiyah as an Islamic basic education institution has a strategic role in shaping the character and competence of students, but the management of Education Operational Costs (BOP) often faces obstacles of transparency, accountability, and limited resources, so that a leadership model is needed that is able to integrate administrative aspects with moral and spiritual values; This study uses a descriptive qualitative approach with interview, observation, and documentation techniques in three madrassas in West Purwokerto District to analyze the implementation of transformative leadership based on prophetic values (siddiq, amanah, tabligh, fathanah) in the management of BOP, with the aim of identifying leadership practices, supporting and inhibiting factors, and practical implications for improving the quality of education; The results of the study show that transformative leadership based on prophetic values is able to improve transparency, accountability, and efficiency of fund management, supported by religious culture, school committees, and government regulations, but still faces obstacles in the form of limited human resources and strict regulations on the use of funds, so this study provides a theoretical contribution to the development of Islamic education management as well as practical recommendations in the form of the need for management training based on prophetic values for madrasah heads and treasurers.